2014
DOI: 10.1002/ceat.201400206
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Piroxicam Solid Forms and the Effects of Additives

Abstract: The relative stabilities of the two anhydrous polymorphs and the monohydrate of piroxicam in ethanol/water mixtures and the crystallization behavior of the solid forms in the presence of 11 additives were studied. At 37°C, form II is thermodynamically more stable than form I, while the relative stability of form II and the monohydrate depends on the water concentration in the solution. The total Hansen solubility parameter d T and the hydrogen bonding solubility parameter d H of the substances can partly expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…It has been reported that the formation of different polymorphs/solvates of an API can be influenced by various operation parameters [1] [11], such as cooling profile, additives, operating mode (i.e. cooling or anti-solvent crystallization), solvents or solvent composition, and the concentration of solute used during the process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the formation of different polymorphs/solvates of an API can be influenced by various operation parameters [1] [11], such as cooling profile, additives, operating mode (i.e. cooling or anti-solvent crystallization), solvents or solvent composition, and the concentration of solute used during the process.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters such as the concentration and type of the additives can influence the occurrence of the different polymorphs [20][21][22]. The additives used for the crystallization process can influence the dissolution rate, the hardness, and therefore even the efficiency of the tablets [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization is a key technology used as a purification and isolation process both on a laboratory and an industrial scale in a wide variety of chemical engineering fields. The solids produced in crystallization processes based on different operation could have various physical and chemical properties such as CSD, crystal morphology, and solid‐state form, which have a strong effect on the final product properties, e.g., dissolution behavior, bioavailability, and density, as well as on the efficiency of the downstream processes such as filtration and drying , .…”
Section: Introductionmentioning
confidence: 99%